Peran Kewirausahaan dalam Meningkatkan Kemandirian Ekonomi Pesantren: Studi Kasus Pondok Pesantren Idrisiyyah - Asiah, Siti Nur; Umar, Mara; Darmawan, Asep (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the role of entrepreneurship in enhancing the economic independence of Islamic boarding schools (pesantren), with a case study at Pondok Pesantren Idrisiyyah in Tasikmalaya. The research uses a descriptive qualitative method, with data collected through observation, interviews, and documentation. The results show that entrepreneurial activities at Pesantren Idrisiyyah include various business units such as agriculture, aquaculture, retail (Qini Mart), culinary services, and Hajj-Umrah travel, all professionally managed and integrated with spiritual values. Entrepreneurship not only contributes financially to the pesantren's operations but also shapes students (santri) into independent and productive individuals. Key success factors include the support of pesantren leadership, active involvement of students and alumni, and innovation in business management. These findings provide a model for sustainable pesantren-based economic empowerment through entrepreneurship.